2012
DOI: 10.1111/j.1369-1600.2012.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroimaging studies of alcohol cue reactivity: a quantitative meta‐analysis and systematic review

Abstract: A comprehensive understanding of the neurobiology of alcohol cue reactivity is critical to identifying the neuropathology of alcohol use disorders (AUD) and developing treatments that may attenuate alcohol craving and reduce relapse risk. Functional neuroimaging studies have identified many brain areas in which alcohol cues elicit activation. However, extant studies have included relatively small numbers of cases, with AUD of varying severity, and have employed many different cue paradigms. We used activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

34
456
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 538 publications
(493 citation statements)
references
References 76 publications
34
456
3
Order By: Relevance
“…These latter regions primarily rely on dopamine, GABA, opioid, and glutamate signaling and are implicated in the development of incentive salience (Kalivas and Volkow, 2005). Further, we found that greater tonic subjective methamphetamine craving was associated with greater activation of the precuneus, a region highlighted by multiple meta-analyses to be reliably involved in cue-reactivity for various substances of abuse (Engelmann et al, 2012;Schacht et al, 2013a). Taken together, these results suggest that this novel paradigm is an effective probe of methamphetamine cueinduced craving in individuals with methamphetamine use disorders.…”
Section: Bold Measures Of Methamphetamine Cue-reactivitymentioning
confidence: 61%
See 2 more Smart Citations
“…These latter regions primarily rely on dopamine, GABA, opioid, and glutamate signaling and are implicated in the development of incentive salience (Kalivas and Volkow, 2005). Further, we found that greater tonic subjective methamphetamine craving was associated with greater activation of the precuneus, a region highlighted by multiple meta-analyses to be reliably involved in cue-reactivity for various substances of abuse (Engelmann et al, 2012;Schacht et al, 2013a). Taken together, these results suggest that this novel paradigm is an effective probe of methamphetamine cueinduced craving in individuals with methamphetamine use disorders.…”
Section: Bold Measures Of Methamphetamine Cue-reactivitymentioning
confidence: 61%
“…The increases in self-reported, subjective methamphetamine craving during the presentation of methamphetamine as compared to control cues highlight the initial efficacy of the task in eliciting cue-induced craving. The primary BOLD results depicted greater methamphetamine (vs control) cue-elicited activation in regions that are commonly seen to be cue-reactive for other substances in dependent populations (eg, middle frontal gyrus, ACC, posterior cingulate cortex (PCC)/precuneus, thalamus, insula, inferior occipital cortex, and brain stem) (Engelmann et al, 2012;Schacht et al, 2013a), and in commonly described 'reward'-or 'reinforcement'-related regions (eg, left ventral striatum (NAcc), bilateral dorsal striatum (caudate, putamen), VTA, hippocampus, and amygdala). These latter regions primarily rely on dopamine, GABA, opioid, and glutamate signaling and are implicated in the development of incentive salience (Kalivas and Volkow, 2005).…”
Section: Bold Measures Of Methamphetamine Cue-reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a large body of literature has examined the human brain structures that respond to such stimuli (for meta-analysis, see Schacht et al, 2012). The taste of an alcoholic beverage is arguably the most proximal conditioned stimulus to the ensuing intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol cue exposure is the most widely used paradigm in fMRI studies of alcoholism (Schacht et al, 2013) and has been shown to elicit activation in the ventral striatum that correlated with self-reported craving (Wrase et al, 2007). Hence, it represents the ideal task to validate the association between subjective responses to alcohol in the laboratory and neural response to alcohol in the scanner.…”
mentioning
confidence: 99%